Marginal Abatement Cost Curve of Industrial CO2 Capture and Storage – A Swedish Case Study - Johnsson, Filip; Normann, Fredrik; Svensson, Elin (Frontiers in Energy Research, 2020)
Carbon capture and storage (CCS) is expected to play a key role to achieve deep emission cuts in the energy intensive industry sector. The implementation of carbon capture comes with a considerable investment cost and a significant effect on the plants operating cost, which both depend on site conditions, mainly due to differences in flue gas flow and composition and depending on the availability of excess heat that can be utilized to power the capture unit. In this study we map the costs required to install and operate amine-based post-combustion CO2 capture at all manufacturing plants in Sweden with annual emissions of 500 kt CO2 or more, of both fossil and of biogenic origin, of which there are 28 plants (including a petrochemical site, refineries, iron and steel plants, cement plants and pulp and paper mills). The work considers differences in the investment required as well as differences in potential for using excess heat to cover the steam demand of the capture process. We present the resulting total CO2 capture costs in the form of a marginal abatement cost curve (MACC) for the emission sources investigated. Cost estimations for a transport and storage system are also indicated. The MACC shows that CO2 capture applied to 28 industrial units capture CO2 emissions corresponding to more than 50% of Swedish total CO2 emissions (from all sectors) at a cost ranging from around 40 €/t CO2 to 110 €/t CO2, depending on emission source. Partial capture from the most suited sites may reduce capture cost and, thus, may serve as a low-cost option for introducing CCS. The cost for transport and storage will add some 25 to 40 €/t CO2, depending on location and type of transportation infrastructure.